(3GdefUhQi aj GdHjRQIs
(3ChdgG (B:s
(3eHJhQ GdChd , hjHOC GdehLhO efg HbQGW (B: (3bGd HGQjG GdeJhcd (B: (3ajbhd (B:(3Ef hGVYi GdcJH ef YdeGA Gdedd GdeJbGOeI de jPcQhG ai cJHge eeGbd PcQg ef MGdGJ PhGJ GdejGSQ s
(3BNQgG (B:s
(3dCf GdeOhO JHJOF HeSjQ GdbeQ ef MO GdeTQb Edi hSW GdSeGA , efg eGjVGa HGdfTGH hGdMQGH ai GdeGA GdUGai aCcd ef GdMhJ LeGYI ? ced GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B254 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs